(untitled) (Research, Society and Development, 2022)
Sheep meat presents variations in qualitative characteristics that influence consumer preference. These characteristics are influenced by ante-mortem factors, such as sex, breed, age at slaughter and feeding; and post-mortem factors, such as meat cooling and storage time and temperature. Twenty-four uncastrated Suffolk lambs were housed in individual corrals and received one of four treatments consisting of four levels of replacement of sorghum silage with wet brewery waste (WBW; 0; 33; 66 and 100% replacement). The diets were isoproteic and contained 18.8% crude protein. The weight and fat proportion in the carcass increased linearly (p≤0.05) while the muscle proportion decreased linearly (p≤0.05) as the WBW levels were increased in the diets. The proximate composition of the meat was not significantly influenced by the WBW levels (P>0.05), except for the ash content which increased linearly (p=0.0003). There was no influence (p>0.05) of the use of WBW on pH, cooking losses and lambs’ meat texture profile. Shear force decreased linearly (p≤0.05). Regarding the meat color, lightness (L*) and redness (a*) were not influenced by the inclusion of WBW. Yellowness (b*) increased linearly (p=0.0038). Regarding the attributes related to lambs’ sensory analysis, there was no effect (p> 0.05) of the inclusion of WBW in the diets. The use of WBW as a bulky food replacing sorghum silage in confined feedlot lambs diet allows the main physical-chemical characteristics related to meat quality to be kept in the normal standards obtained for ovine species.